Estudio digital radiográfico y densitométrico en mandíbulas de cerdos sometidos a osteotomía con alta y baja velocidad, con refrigeración líquida - Monti, Lira Marcela [UNESP]; Castro, Alvimar Lima de [UNESP]; Louzada, Mário Jefferson Quirino [UNESP]; Salzedas, Leda Maria Pescinini [UNESP] (Inspira Network Group, 2010)
The influence of the type of rotary cutting instrument on bone repair after osteotomy in swine jaw, was evaluated using digital and densitometric radiographic examinations, at controlled times. Two cross-sectional dissections were made through the base of the right jaw, one using a high speed rotary instrument and the other using low speed, both with liquid cooling. After established periods the animals were sacrificed and their jaws removed for direct and indirect digital radiographic and densitometric studies using the CROMOX, DIGORA and ODR systems. In the initial periods (7 and 28 days) the bone density was higher in osteotomy areas performed with high rotation speeds, and in the final periods (60 and 90 days) the bone density was higher in the osteotomies performed with low rotation, indicating a better final bone repair with the use of low rotation. The qualitative analysis of the repair process was made by the ODR system which obtained three-dimensional and coloured digital images, which enable the bone thickness to be measured using an aluminium wedge. This showed that by twenty-eight days the bone repair was already apparently complete. © 2010 SECOM.
Digital and densitometric radiographic study in swine jaws subjected to osteotomy using high and low drilling speeds with liquid cooling
Keywords: Bone density; Osteotomy; Radiographic image enhancement; Swine